2017
DOI: 10.1186/s13065-017-0304-2
|View full text |Cite
|
Sign up to set email alerts
|

A comparative study of the metal binding behavior of alanine based bis-thiourea isomers

Abstract: Two new symmetrical bis-thiourea, 2,2′-[{(terephthaloylbis(azanediyl)bis(carbonothioyl) bis(azanediyl)}dipropanoic acid] (1A) and 3,3′-[{(terephthaloylbis(azanediyl)bis (carbonothioyl)bis(azanediyl)} dipropanoic acid] (1B) were synthesized by the reaction of terephthaloyl chloride with α- and β-alanine in good yields. Their binding properties were investigated with various metal cations using UV–Vis titration experiments. Both isomers exhibited effective binding with Ag+, Cu2+, Hg2+, Pb2+, Fe2+ and Fe3+ cation… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
4
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 16 publications
(4 citation statements)
references
References 28 publications
0
4
0
Order By: Relevance
“…These absorption bands undergo both bathochromic and hypsochromic shifts of +20/21 and - (10)(11)(12)(13)(14)(15)(16)(17)(18)(19)(20)(21)(22) nm relative to their chloride counterparts (green curves in Fig. 2) studied in our previous publications [17,19].…”
Section: Resultsmentioning
confidence: 82%
See 1 more Smart Citation
“…These absorption bands undergo both bathochromic and hypsochromic shifts of +20/21 and - (10)(11)(12)(13)(14)(15)(16)(17)(18)(19)(20)(21)(22) nm relative to their chloride counterparts (green curves in Fig. 2) studied in our previous publications [17,19].…”
Section: Resultsmentioning
confidence: 82%
“…A recent trend in the development of new metal-based anticancer drugs is the use of biologically active ligands capable of inhibiting the growth of malignant tumors with different mechanisms of action [10,11]. Promising ligands for the development of new potential drugs are thiourea derivatives, which, having high antitumor activity [12], are able to coordinate many metal ions as N,S donor agents [13][14][15]. In previous studies, we found that a number of π-coordination complexes of Pt(II) and Pd(II) with N-allylthiourea derivatives showed a high affinity to DNA with cytostatic and proapoptotic effects which was superior to that of cisplatin [16][17][18][19].…”
mentioning
confidence: 99%
“…Derivative 1A, however, showed no excellent biological activity against various bacteria. It is assumed from the structure of similar bis-thiourea derivative (Fakhar et al 2017) that the thiourea moiety is not planar because of intermolecular attractions hence offering steric hindrance. The occurrence of steric hindrance creates a force that obstructs the contact between active sites in the compound with receptor site of the bacteria (Fernandez et al 2005).…”
Section: Anti-bacterial Studiesmentioning
confidence: 99%
“…The band at 370 nm shows a hyperchromic effect with an increasing amount of Hg 2+ . Based on the UV-Vis titration, we were able to calculate the stoichiometry of the binding interaction between ligand 3b and Hg 2+ through the molar-ratio curve method (Figure 4) [19]. The binding ratio of 3b-Hg 2+ was 1:1 and the binding constant (K d ) was calculated using the nonlinear regression equation using Sigma Plot 12.0 software.…”
Section: Binding Behaviors For 3b Towards Some Selected Metal Ionsmentioning
confidence: 99%